DESIGNING ENGLISH LEARNING WORKSHEETS FOR READING AND WRITING SKILLS QUALIFYING ON HOTS FOR THE TENTH GRADE STUDENTS - Arita Destianingsih (INOVISH JOURNAL, 2016)
Abstract: The aims of this study are to find out the learning needs of the tenth grade students and to develop effective English learning worksheets for reading and writing skills qualifying on higher order thinking skills (HOTS) for the tenth grade students. This research and development (R&D) adopted the model research proposed by Dick, Carey, & Carey (2009) and Branch (2009). This study was conducted at SMA Negeri 1 Pakem, Sleman. The effectiveness of the product was obtained through students’ English pretest and posttest score. There was the experiment class (XMIA1) and control class (XMIA2) group design. The mean score for pretest of the experimental class was 47.44, while the control class was 43.91. After learning using HOTS worksheets in the experimental class the mean obtain in the posttest was 90.56, while in the control class was 50.31.  The improvement of learning outcomes from the mean of N -Gain in experimental class was 0.81 in high category and the control class was 0.10 in low category. In the control class and experiment class had different learning result significantly. The result of the students’ agreements toward the product is within the data interval  ≥ 3.28 in good category. It can be concluded that the product are fairly effective to be applied in English teaching and learning processes.Keywords: Needs analysis, higher order thinking skills, designing English learning worksheet